Antireflux surgery for prevention of chronic lung allograft dysfunction (CLAD) onset after lung transplantation: The earlier the better before CLAD onset? A single-center series of 284 patients - Abdulmonem Hamid; Alexandre Vallée; Sophie Rong; Olivier Boche; Sandra De Miranda; Laurence Beaumont-Azuar; Sylvie Colin de Verdière; Dominique Grenet; Marc Stern; Benjamin Zuber; Jerôme Devaquet; Julien Fessler; et al. (JHLT Open)
Background: Gastroesophageal reflux disease (GERD) is highly prevalent after lung transplantation (LTx) and is suspected to favor the development of chronic lung allograft dysfunction (CLAD), almost of bronchiolitis obliterans syndrome (BOS) phenotype. The preventive effect of antireflux surgery (ARS) on BOS/CLAD onset in patients with GERD still remains debated. We compared the outcome (freedom from CLAD and graft survival) of patients with GERD with or without performed ARS (GERD-ARS and GERD-noARS groups) and those without GERD (noGERD group) in our LTx cohort. Methods: Data from 284 LTx recipients with available post-LTx pHmetry findings were reviewed (2001-2014). We focused on the outcome of 244 patients without CLAD at the date of pHmetry. Results: Among 244 stable patients at the date of pHmetry, 78 patients did not have GERD and 166 patients had GERD [41 with and 125 without ARS performed]). The mean DeMeester score was higher in the GERD-ARS group than GERD-noARS group (p = 0.03). An increase in donor-specific antibodies' mean fluorescence intensity values was observed only in GERD after LTx (M6 vs day 0, p < 0.0001; M12 vs day 0, p = 0.003). Freedom from CLAD at 3 years post-pHmetry/ARS was higher for GERD-ARS patients as compared to GERD-noARS patients (p = 0.002). Additionally, ARS was independently associated with a subsequent decreased risk of CLAD onset at 3 years in GERD patients (GERD-ARS vs GERD-noARS, p = 0.02 [Cox models]). ARS was safe in this series, with no surgery-related deaths. Conclusions: Our results suggested a preventive effect of ARS on CLAD onset in stable selected patients with GERD, with a beneficial medium-term effect. IRB approval number: IRB00012437